PSR DAN ZPR SEBAGAI IPI PADA PROFITABILITAS DENGAN MODERATOR INTELLECTUAL CAPITAL - Lutfiatul Inayah; Maretha Ika Prajawati (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2023)
The development of sharia in Indonesia is improving, and must use financial performance measurements by sharia principles, one of which is the Islamicity performance index. This study examined Islamicity Performance's impact on Islamic commercial banks' profitability by adding intellectual capital as a moderating variable. This research utilises data from 10 Islamic Commercial Banks (BUS) recorded at the OJK in 2017-2021 after purposive sampling. The method used in this research is panel data regression analysis and MRA. The results show that the Profit-Sharing Ratio (PSR) has no effect on profitability, Zakat Performance Ratio (ZPR) has an impact on profitability, and Intellectual Capital (IC) can moderate the influence of both independent variables on profitability. Based on the findings that have been described, it is hoped that this will become a consideration for company management to increase PSR and ZPR, indicators of a company's Islamic financial performance, by raising intellectual capital.